(untitled) (Research, Society and Development, 2021)
In this study evaluated the effect of different adhesive systems and resin composites on the microtensile bond strength of repairs using a bulk-fill composite. Ninety specimens were prepared using a half-hourglass mold of composite Filtek Bulk Fill using a silicone matrix. Specimens were randomly distributed in 9 experimental groups (n=10) according to adhesive [Universal Single Bond (SBU), Scotchbond Multipurpose Adhesive (SBMP), and Single Bond 2 (SB2)] and resin composite (Filtek Bulk Fill, Aura Bulk Fill, and Filtek Z250). For control group, hourglass specimens were used to measure the ultimate bond strength. Specimens were submitted to thermal cycling (5,000 cycles, 5 and 55°C, 30s) to simulate the aging of restoration and then the repair procedure was performed. After the diamond-tipped surface roughening to be repaired, the adhesive protocol was performed according to group, the specimen was placed in an hourglass-shaped mold and the other half was filled with the repair composite. After 24h, bond strength of specimens was obtained by microtensile using a universal testing machine at a speed of 0.5mm/min. Data were statistically analyzed by two-way ANOVA, Tukey’s and Dunnett’s tests (α=0.05). SBU showed higher bond strength compared to SB2, while SBMP showed intermediate values. However, all experimental groups showed lower bond strength compared to ultimate bond strength. In conclusion, bulk-fill composite repair using universal or conventional solvent-free adhesive improved the adhesion independent of composite tested.